(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1866)
Chapter IX: Import of the Ring and Cup Cuttings Chapter X: Their Alleged Phoenician Origin Chapter XI: Their Probable Ornamental Character Chapter XII: Their Possibly Religious Character Chapter XIII: Question of their Age or Date Chapter XIV: Their Precedence of Letters and Traditions Chapter XV: Their Connection with Archaic Towns and Dwellings Chapter XVI: Their Presence on the Stones of the most Ancient Kinds of Sepulture Chapter XVII: The Archaic Character of the Contemporaneous Relics found in Combination with them Chapter XVIII: The Kind of Tools Required for the Sculpturings Chapter XIX: Their Antiquity, as shown by their Geographical Distribution in the British Islands Chapter XX: The Race that first Introduced the Lapidary Ring and Cup Sculpturings